PERSEPSI MASYARAKAT TERHADAP KUOTA 30 PERSEN KETERWAKILAN PEREMPUAN DI LEGISLATIF - Afrina Sari (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2010)
This research to analyze people's perception of the quota of 30 percent women representation in legialatif. The method used is descriptive method that analyzed based on a statistical analysis of data kuantutatif The results showed that there are differences in perceptions that distinguish between women activists and activists of men over 30 per cent quota of women representation in the legislature